2018
DOI: 10.2147/dddt.s173485
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic drug targeting to lungs by way of microspheres after intravenous administration

Abstract: PurposeCurrently, microsphere technology plays a major role in the development of many new cancer therapies. In the current study, we proposed a targeted drug-delivery system to improve the treatment efficacy of one of the common conventional chemotherapeutic drugs used to treat lung tumors, 5-fluorouracil (5-FU).Materials and methodsFollowing the preparation and optimization of small, solid micro-spheres, ranging in diameter between 5 and 15 µm, the final product 5-fluorouracil gelatin (5-FUG) was formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Additionally, a trend can be seen where an increase in voltage leads to a decrease in uniformity ( Figure 1 ). An increase in spray voltage leads to a rise in the repulsive force between droplets due to ion movement towards the droplet surface, leading to the instability of the jet at high voltages [ 35 ]. As shown in Figure 1 , to achieve the best uniformity, a lower flow rate and voltage should be chosen.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a trend can be seen where an increase in voltage leads to a decrease in uniformity ( Figure 1 ). An increase in spray voltage leads to a rise in the repulsive force between droplets due to ion movement towards the droplet surface, leading to the instability of the jet at high voltages [ 35 ]. As shown in Figure 1 , to achieve the best uniformity, a lower flow rate and voltage should be chosen.…”
Section: Resultsmentioning
confidence: 99%
“…The particle size of the microspheres is the main important factor as it controls the tissue location of the microspheres after intravenous administration. Previous reports have proved that microspheres with the size range of 5–25 μm have a notable lung targeting due to mechanical trapping in the fine blood capillaries of the lung [ 17 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to nanoparticles, microspheres offer a well-established platform technology for easy commercialization and effective delivery by oral, parenteral as well as nasal routes [15,16]. The methodology applies to a wide range of therapeutics with diverse physicochemical properties like small antibiotic molecules and peptides, and proteins [17]. Huo et al [18] showed that cisplatin-loaded biodegradable PLGA microspheres could achieve successful accumulation of particles in lungs after parenteral administration along with a sustained release for effective long-term therapy to reduce the frequency of dosing.…”
Section: Introductionmentioning
confidence: 99%
“…Sriram et al demonstrated that hydrophobic drugs could be encapsulated in microspheres and administered intravenously to treat disease [5]. Sibghatullah et al used the method of spray drying to prepare gelatin microspheres encapsulating 5-fluorouracil with the particles size range of 5-15 µm for the treatment of lung cancer by intravenous injection, and the results showed that the drug-loaded microspheres improved the release time of the drug [6]. Thus, AKI therapy by intravenous injection of SAHA-loaded calcium alginate microspheres is a promising method.…”
Section: Introductionmentioning
confidence: 99%